Pengaruh Konsumsi Rumah Tangga, Pengeluaran Pemerintah Dan Pendapatan Perkapita Terhadap Pertumbuhn Ekonomi Provinsi Jambi - Sabyan, Muhammad; Amrizal, Amrizal; Wiarta, Iqra (CV. ITTC INDONESIA, 2022)
This study aims to see how the influence of household consumption, government spending and per capita income on economic growth in Jambi province, after doing research using the multiple linear regression formula, the answer was found that partially only household consumption expenditure variables have a significant effect on increasing economic growth of Jambi Province. While the rest have no significant effect. However, together the variables of household consumption expenditure, government expenditure and per capita income have a significant effect on the economic growth of Jambi Province with an R-square value of 99.50 percent during the 2010-2020 period.